Phenotypic Plasticity and Functional Shift in Cisplatin-Resistant Cervical Cancer Cell Line - Kristiani, Lidya; Ivana, Kathy; Gabriela, Vania; Rattu, Shereen Angelina; Tanoto, Joselyn Phoebe Wylma; Dearyza, Sonya; Angelica, Rosemarie; Wirabuana, Shareena; Dreesa, Amelia; Tehubijuluw, Marcella Diviani; Crystalia, Audrey Amira (Indonesian Journal of Cancer, 2026)
Background: Cervical cancer remains the deadliest cancer among women. Furthermore, the development of resistance toward cisplatin, the golden standard treatment, has posed a significant challenge, threatening therapeutic efficacy and contributing to tumor recurrence. While enhanced DNA repair and drug inactivation have been implicated in resistance, their impact on cervical cancer remains poorly understood. This study aims to generate cisplatin-resistant cervical cancer cell lines to explore potential phenotypic and functional changes.Methods: We generated cisplatin-resistant cells through repeated exposure to increasing cisplatin concentrations up to 8 µM. Morphological changes were analysed using ImageJ software. Using manual hemocytometer counting, we generated a growth curve to assess cell growth, while a migration assay measured wound closure over time. Mitochondrial activity was evaluated using the MTS (3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium) assay, and gene expression of p53, Bax, and β-actin was quantified via qPCR. Statistical analysis, including two-tailed Student’s t-tests, was performed to compare wild-type and treated groups, with significance at p 0.005. Graphs and data visualization were performed using Microsoft Excel and GraphPad Prism 10.2.3.Results: Cisplatin-resistant (CPR) HeLa cells exhibited concentration-dependent morphological changes, including multinucleated "giant cells" and neuron-like "transition cells" with extended arms, suggesting adaptive responses to cisplatin-induced stress. Cell size increased with higher cisplatin concentrations, potentially enhancing survival, while proliferation decreased, indicating an energy trade-off for resistance mechanisms. Mitochondrial activity declined in CPR cells, likely due to mitochondrial DNA damage, leading to reduced ATP production and oxidative stress. Gene expression analysis revealed decreased Bax levels, associated with reduced apoptosis. Despite these changes, migration capacity remained unchanged.Conclusions: The results reveal that cisplatin-resistant (CPR) HeLa cells develop distinct changes in characteristics, including morphologies and functional capacity, particularly decreased mitochondrial activity and proliferation in exchange for increased ability to avoid apoptosis. These findings deepen our understanding of cisplatin resistance and emphasize the need for innovative therapeutic strategies, such as targeting the altered characteristics and non-proliferative survival mechanisms of CPR cells.